Kinetics of austenite decay during continuous cooling of undeformed boron-containing steel 30G1R - Sobolenko , M.O.; Romanova , N.S. (Theory and Practice of Metallurgy, 2023)
Purpose. Conduct a study on the kinetics of decomposition of undeformed supercooled austenite during continuous cooling of boron-containing steel. Establish the patterns of structure formation in boron-containing steel during continuous cooling at various rates from heating temperatures. Methodology. The study of phase transformations and the kinetics of decomposition of undeformed supercooled austenite was conducted using differential thermal analysis on samples of boron-containing steel, accompanied by investigations of microstructure and hardness. Findings. The kinetics of transformations were studied, and thermokinetic diagrams of the decomposition of undeformed supercooled austenite in boron-containing steel were constructed. Critical points were examined, and the peculiarities of the influence of the cooling rate of undeformed austenite on the volume fraction of structural components in boron-containing steels were identified. Originality. The positions of critical temperature points have been demonstrated, and both qualitative and quantitative depictions of the structure formation of the investigated boron-containing steel have been obtained. The influence of cooling rate on the nature of austenite transformations and the mechanical properties of the studied steel has been revealed. Practical value. The conducted research (knowledge of the positions of critical points) enables the targeted selection of heating, cooling, and isothermal holding temperatures during the development of annealing regimes both in the subcritical temperature range and with partial or complete phase recrystallization. The obtained results can be utilized in designing various thermal treatment regimes applied in industrial technologies for the production of coiled rolled products made from boron-containing steel for cold forging.